2022
DOI: 10.3390/pr10020341
|View full text |Cite
|
Sign up to set email alerts
|

Broken Riceberry (BR) Powder Production Using a Double Drum Dryer and Its Utilization in the Development of Instant Beverages

Abstract: This study was designed to examine broken riceberry (BR) powder production through the use of a double drum dryer. There were two stages involved: (1) to study the optimized drum drying conditions for BR powder using response surface methodology (RSM), and (2) to utilize BR powder for the development of instant beverages. According to the results, the optimum drum drying condition was a drum temperature of 125 °C and drum speed of 1.0 rpm. Under these conditions, BR powder contained moisture = 5.81%, water act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Color is a major quality parameter in a dried food product; color was presented in terms of L*, a*, and b*, which implied that the Riceberry bran powder was pink powder. These data agreed with the reports from Rittisak, Charoen, and Savedboworn (2022). Their study reported the optimal condition for broken Riceberry powder preparation as using a double drum dryer at 125C and a drum speed of 1.0 rpm.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Color is a major quality parameter in a dried food product; color was presented in terms of L*, a*, and b*, which implied that the Riceberry bran powder was pink powder. These data agreed with the reports from Rittisak, Charoen, and Savedboworn (2022). Their study reported the optimal condition for broken Riceberry powder preparation as using a double drum dryer at 125C and a drum speed of 1.0 rpm.…”
Section: Discussionsupporting
confidence: 90%
“…Under their conditions, the broken Riceberry powder contained moisture content and water activity of less than 10 and 0.6, respectively. Their broken Riceberry powder was also found as pink powder (Rittisak et al, 2022). The results on chemical properties obviously displayed that using a double drum dryer to prepare Riceberry bran powder did not demolish the activities on anti--glucosidase, antioxidants against DPPH and ABTS radicals, or phenolic content.…”
Section: Discussionmentioning
confidence: 98%
“…Rittisak et al [4] proposed riceberry as a raw material for broken riceberry powder production by using a drum dryer after pregelatinization. The potential of the resultant powder was examined for the development of a novel instant beverage.…”
mentioning
confidence: 99%